Analisis Efektivitas Biaya Antara Non-Tunneled Hemodialysis Catheter dengan Tunneled Hemodialysis Catheter di RS Fatmawati Bulan Juni-Juli 2024: Analisis Efektivitas Biaya Antara Non-Tunneled Hemodialysis Catheter dengan Tunneled Hemodialysis Catheter di RS Fatmawati Bulan Juni-Juli 2024 - Yulianti, Dwi; Rahmawati, Intan Rizqi (RSUP Fatmawati, 2024)
Hemodialysis is one of the life-saving treatment for kidney failure. Hemodialysis catheters are an essential part of hemodialysis access, there are two types of catheter hemodialysis: non-tunneled hemodialysis catheter and tunneled hemodialysis catheter. Hemodialysis catheter sometimes causes complications include infection or dysfunction. Therefore, researchers need to determine the Cost Effectiveness Analysis of non-tunneled hemodialysis catheter and tunneled hemodialysis catheter. This research is descriptive study with retrospective data collection from patient medical record and hospital billing. The research was conducted on inpatients with the installation of non-tunneled hemodialysis catheter and tunneled hemodialysis catheter at Fatmawati Hospital in June-July 2024 using Average Cost Effectiveness Ratio and Incremental Cost Effectiveness Ratio methods. From the result, patient who used hemodialysis catheters at Fatmawati Hospital were more male (54%) with an age group of <65 years (87%). The most comorbidities are diabetes mellitus, hypertension and anemia with 25,72% each. Tunneled hemodialysis catheter is the most cost effective for supporting hemodialysis in patients with end stage chronic kidney disease at Fatmawati Hospital, as evidenced by a smaller ACER value Rp. 362,691 and a negative ICER value -3,299,583 and include category of cost effectivess grid G cells which means dominant in cost effectiveness.